2019
DOI: 10.1186/s12967-019-1800-z
|View full text |Cite
|
Sign up to set email alerts
|

A two-circular RNA signature as a noninvasive diagnostic biomarker for lung adenocarcinoma

Abstract: Background Recently, circular RNAs (circRNAs) have been reported to be microRNA sponges and play essential roles in cancer development. This study aimed to evaluate whether circulating circRNAs could be used as diagnostic biomarkers for lung adenocarcinoma (LUAD). Methods The Gene Expression Omnibus (GEO) dataset was used to investigate differentially expressed circRNAs (DEcircRNAs) in paired LUAD tissues and adjacent nontumor tissues. The expression levels of the host … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 53 publications
1
73
0
Order By: Relevance
“…Previous studies have demonstrated that circRNAs may be closely connected with the development cancers . Among them, circ‐SMARCA5, the circRNA derives from exons 15 and 16 of SMARCA5 gene, is found to be related to the disease progression in a few cancers .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that circRNAs may be closely connected with the development cancers . Among them, circ‐SMARCA5, the circRNA derives from exons 15 and 16 of SMARCA5 gene, is found to be related to the disease progression in a few cancers .…”
Section: Discussionmentioning
confidence: 99%
“…Although these studies display downregulated expressions of circ‐SMARCA5 in some cancers, the involvement of circ‐SMARCA5 in lung cancer has not been clearly clarified, and only one study shows that circ‐SMARCA5 is downregulated in NSCLC tissues compared to the adjacent normal tissues, and it inhibits cell proliferation, migration as well as invasion in NSCLC cell lines . Some recent studies have implied that non‐coding RNAs, especially circRNAs, play crucial roles in pathology and progression of NSCLC . For example, long non‐coding RNA KDM5B anti‐sense RNA 1 enhances tumor progression in NSCLC; circular RNA F‐circSR derived from SLC34A2‐ROS1 fusion gene enhances cell migration in NSCLC; overexpression of circular RNA FARSA promotes NSCLC cell migration and invasion .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that the role of several circRNAs was partly characterized, there were still existing circRNAs lacking functional exploration. A previous study predicted differentially expressed circRNAs in lung adenocarcinoma using Gene Expression Omnibus (GEO) dataset and found that circ_0005962 was highly expressed in lung adenocarcinoma plasma and cells (Liu et al, 2019). In view of this finding, we speculated that dysregulation of circ_0005962 might be associated with the malignant progression of NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…CircRNA F-circEA-2a contributed to cell migration and invasion but had little role in cell proliferation (Tan et al, 2018). A former study obtained dozens of circRNAs through the CircBase database and CSCD database for comparison between lung adenocarcinoma tissues and paired non-tumor tissues (Liu et al, 2019), and circ_0005962, back-spliced from tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activation protein zeta (YWHAZ), was one of the significantly upregulated circRNAs and had valuable prognostic significance. However, the understanding of the specific roles of circ_0005962 in NSCLC remains lacking and requires further exploration.…”
Section: Introductionmentioning
confidence: 99%
“…30 Increasing evidence suggested that circRNA might participate in the cell proliferation, migration and invasion of lung cancer, and serve as an important diagnostic marker for the treatment of lung cancer. [31][32][33][34][35][36][37] For example, circNOL10 increased the expression of transcription factor sex comb on midleg-like 1 (SCML1) by inhibiting ubiquitination and regulating the humanin (HN) polypeptide family through affecting multiple signaling pathways. This ultimately inhibited proliferation and induced cell cycle arrest in lung cancer cells.…”
Section: Acting As Autophagy Regulatormentioning
confidence: 99%